Comparison between Mycophenolate Mofetil and Azathioprine for Preventing Renal Relapse in Lupus Nephritis: An Evidence-based Case Report - Bambang Setiyohadi; Muhammad Aji Muharrom (Indonesian Rheumatology Association, 2018)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease which involved many organs. One of its severe manifestations is lupus nephritis (LN). Treatment of LN consists of two phases, induction and maintenance. Inappropriate treatment approach could increase morbidity and mortality in LN patients. Renal flare is among many bad outcomes of LN that should be mitigated with an appropriate therapeutic approach. Various guidelines stated usage of mycophenolate mofetil (MMF) or azathioprine (AZA) as an appropriate immunosuppresant in the maintenance phase. However, it is not clear which agent acts best in preventing renal flare. This paper presents a case of 21 years old SLE female patient with history of renal flare 1 month prior to admission. This study aimed to give evidence-based recommendation to adjust this patient’s therapy in order to prevent future renal flare episode. Method: Literature search was done on four online databases, namely PubMed, EBSCO, Cohrane Library, and ProQuest. Articles with randomized clinical trial (RCT), systematic review and meta-analysis study design were retrieved and selected based on inclusion and exclusion criterias. Critical appraisal was done using appraisal sheet provided by Oxford Centre of Evidence-based Medicine. Articles were appraised based on its validity, importance, and applicability.Results: There were 144 articles retrieved from literature searching. Further screening and full-text reading yields to 2 RCTs and 2 meta-analysis that were critically appraised. Both meta-analysis were satisfactory on their validity, while none of RCTs found were blinded studies. Both meta-analyses showed pooled risk ratio (RR) of0.70 (0.49 – 1.00) for renal flare outcome in the use of mycophenolate mofetil compared to azathioprine. Conclusion There are no significant differences between mycophenolate mofetil and azathioprinein prevention of renal flare. Based on applicability, azathioprine is more appropriate to be given in this patient, in accordance to her background.Keywords : Lupus Nephritis, Renal Flare, Mycophenolate Mofetil, Azathioprine, Systemic Lupus Erythematosus